Leónidas Lamborghini, Risa y tragedia en los poetas gauchescos. Hidalgo, Ascasubi, Del Campo, Hernández. Emecé, Buenos Aires, 2008; 140 pp. - Sosa, Carlos Hernán (El Colegio de México, 2009)
Se reseñó el libro: Risa y tragedia en los poetas gauchescos : Hidalgo, Ascasubi, Del Campo, Hernández.